Pediatric Deceased Donation—A Report of the Transplantation Society Meeting in Geneva. Issue 7 (July 2015) - Martin, Dominique E.; Nakagawa, Thomas A.; Siebelink, Marion J.; Bramstedt, Katrina A.; Brierley, Joe; Dobbels, Fabienne; Rodrigue, James R.; Sarwal, Minnie; Shapiro, Ron; Dominguez-Gil, Beatriz; Danovitch, Gabriel; Sweet, Stuart C.; et al.
<x xml:space="preserve">Abstract</x> The Ethics Committee of The Transplantation Society convened a meeting on pediatric deceased donation of organs in Geneva, Switzerland, on March 21 to 22, 2014. Thirty-four participants from Africa, Asia, the Middle East, Oceania, Europe, and North and South America explored the practical and ethical issues pertaining to pediatric deceased donation and developed recommendations for policy and practice. Their expertise was inclusive of pediatric intensive care, internal medicine, and surgery, nursing, ethics, organ donation and procurement, psychology, law, and sociology. The report of the meeting advocates the routine provision of opportunities for deceased donation by pediatric patients and conveys an international call for the development of evidence-based resources needed to inform provision of best practice care in deceased donation for neonates and children.